Probing the structure, conformation, and stereochemical exchange in a family of lanthanide complexes derived from tetrapyridyl-appended cyclen. - Natrajan, L; Khoabane, N; Dadds, B; Muryn, C; Pritchard, R; Heath, S; Kenwright, A; Kuprov, I; Faulkner, S (2010)
A series of lanthanide complexes have been synthesized from 1,4,7,10-tetrakis(2-pyridylmethyl)-1,4,7,10-tetraazacyclododecane. Crystallographic studies indicate that, in the solid phase, all of the lanthanide ions are 9-coordinate and are bound to eight N atoms from the donor ligand, with the ninth site being filled by a counterion or solvent molecule. In solution, time-resolved luminescence studies indicate that the luminescence exhibits contributions from two species corresponding to the nonhydrated and hydrated forms. The NMR spectra in protic media show the presence of two dominant isomers on the NMR time scale; furthermore, the spectra are very different from those obtained for 1,4,7,10-tetraazacyclododecane-N',N'',N''',N''''-tetraacetic acid (DOTA) and its derivatives. The different forms of the complex undergo slow conformational and enantiomeric exchange in solution, which has been measured by NMR. The exchange path has been mapped out by density functional theory calculations and shows multiple metastable conformations (with respect to the dihedral angles of the cyclen ring). This contrasts with the established NMR behavior of DOTA complexes, which has been described by a two-state solution equilibrium.